Temporomandibular dysfunction in patients with a history of stroke. - Ramos, Mariana Altvater; Moura, Beatriz Garcia; Araujo, Camila Costa; Antonio, Tiago Tsunoda Del; Silva, Joyce Karla Machado da (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: The temporomandibular joint (TMJ) is certainly one of the most complex joints in the human body. The American Academy of Orofacial Pain defines temporomandibular joint disorder (TMD) as a set of disorders involving the masticatory muscles, the TMJ, and associated structures. It is pointed as the main cause of non-dental pain in the orofacial region, including head, face and related structures. The most common TMD symptoms involve joint, chewing and face pain. There may also be crackling when opening and closing the mouth, earache, tinnitus, dizziness, dislocations, limitation of movement and painful tenderness to palpation. Stroke causes sequelae in subjects that include motor disorders, speech or language disorders, and swallowing disorders. Approximately 50% of patients with hemiparesis after stroke are known to have facial control deficiency, weakened orofacial and mandibular functions. Objective: To evaluate patients with a history of stroke, seeking a possible relationship with TMD, the pain associated with this change, and the limitations of range of motion related to the presence of hemibody spasticity in patients post stroke. Methods: The sample consisted of 19 patients of both genders, aged 55 to 70 years, who had suffered stroke. It was used the RDC/TMD for TMD diagnosis, Pressure Pain Threshold test, Ashworth scale, and Sanny Fleximeter for cervical ROM evaluation, being the statistical analysis performed by the software Bioestat version 5.3. Results: TMD was diagnosed in 81.8% of the sample, and of these, 45.4% had a diagnosis of disc displacement with reduction. Conclusion: There was an increase in the muscle tone and the pressure pain threshold, and a decrease in cervical spine ROM, related to the affected side and diagnosed with this disorder, observing that the muscle alterations caused by stroke may be predisposing factors to patients, to the development of muscle TMD or even joint TMD.